Folk Culture in the Digital Age : The Emergent Dynamics of Human Interaction - Blank, Trevor J. (Book collections on Project MUSE., 2012)
Smart phones, tablets, Facebook, Twitter, and wireless Internet connections are the latest technologies to have become entrenched in our culture. Although traditionalists have argued that computer-mediated communication and cyberspace are incongruent with the study of folklore, Trevor J. Blank sees the digital world as fully capable of generating, transmitting, performing, and archiving vernacular culture. Folklore in the Digital Age documents the emergent cultural scenes and expressive folkloric communications made possible by digital "new media" technologies. New media is cha.